Bust of John Steinbeck on Cannery Row - Vinnie Lopez:::Photographer::::::::::::; Steven Domingo:::Photographer:::::::::::: (Monterey, California, 2023)
Photograph of the Bust of John Steinbeck on Cannery Row, Monterey. The bust was donated to the people of Monterey in 1972 by Mr and Mrs Merle W Strauch, Sculptor C W Brown